2014
DOI: 10.4149/bll_2014_048
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of pemetrexed-based doublet compared with pemetrexed alone for the second-line treatment of advanced non-small-cell lung cancer

Abstract: Abstract:Purpose: This meta-analysis investigated pemetrexed-based doublet compared with pemetrexed alone as second-line therapy for patients with advanced non-small cell lung cancer. Methods: Randomized controlled trials which compared pemetrexed-based doublet with single-agent pemetrexed in patients as second-line treatment of advanced non-small cell lung cancer were searched. Overall survival (OS) was the primary end point, while secondary end points included progression-free survival, overall response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For instance, Klionsky et al reported that there was no significant difference in terms of thrombocytopenia between docetaxel and pemetrexed; however, Sun et al reported docetaxel caused a higher rate of thrombocytopenia. 38 , 39 In order to obtain a precise result, we only included large-sample Phase III trials for toxicity assessment. It also led to anemia compared with pemetrexed as the first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Klionsky et al reported that there was no significant difference in terms of thrombocytopenia between docetaxel and pemetrexed; however, Sun et al reported docetaxel caused a higher rate of thrombocytopenia. 38 , 39 In order to obtain a precise result, we only included large-sample Phase III trials for toxicity assessment. It also led to anemia compared with pemetrexed as the first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 10 19 However, the conclusion drawn from these small-sample-size studies were inconsistent. Although previous meta-analyses conducted by Qi et al 20 and Sun et al 21 showed that the combination of pemetrexed and chemotherapy was not superior to single-agent pemetrexed as a second-line treatment for NSCLC, these analyses only included four and five studies, respectively, which is only ~50% of the available data. In addition, subgroup and sensitivity analyses were not performed, so the results might not be robust.…”
Section: Introductionmentioning
confidence: 99%